Case Study on the Academic Supervision of School Teachers Utilizing Coaching Techniques to Sustain Learning Quality in Elementary Education - Widatin, Tri; Roemintoyo; Sukarno (Journal of Education Reseach and Evaluation, 2025)
Many elementary schools struggle to improve teaching quality due to the limited impact of conventional, top down supervision models that lack alignment with teacher development needs, thereby hindering reflective practice and teacher autonomy issues that coaching based supervision, with its emphasis on partnership, dialogue, and empowerment, seeks to address. This study is to delineate the implementation process of coaching supervision, investigate the experiences of educators and administrators, and assess its effects on teacher performance and the quality of learning in Elementary School. Data were gathered via in depth interviews, participatory observation, and documentation, there after analyzed interactively according to the Miles and Huberman approach. The study's findings indicated that coaching supervision was conducted systematically, adhering to the concepts of equitable partnership, innovative discussion, and teacher empowerment, which fostered profound reflection and professional autonomy. This supervisory technique fostered a collaborative environment that facilitated innovation in daily educational practices. A notable beneficial effect was observed from the enhancement of teacher performance and the quality of education at the school, however adaptation issues persisted, particularly around shifts in roles and mindsets. On going support and training are crucial elements in surmounting these challenges. The results of this study are anticipated to serve as a benchmark for other primary schools in creating a more adaptive, efficient, and sustainable supervision model to enhance elementary education overall.